Improved prediction of pre-camber of post-tensioned prestressed I-beam - Omar, Wahid; Tan, Pui Lai; Lee, Poh Huat; Omar, Roslina (The Institution of Engineers Malaysia, 2008)
An improved method of calculating pre-camber prediction in prestressed concrete beam is presented. It has been found that the current method of estimation that is widely practiced by local engineers which is based on BS 8110 is over simplified and inaccurate. Accurate prediction of the upward deflection or pre-camber due to prestressing of prestressed concrete beams is always difficult to attain. Inaccurate estimation of pre-camber usually leads to complications in construction and may incur additional cost. This paper presents an improved pre-camber prediction of prestressed I-beam that adopts the equivalent weight method with the inclusion of concrete creep factor into the deflection equation. While creep is often ignored or underestimated, it is being considered in the calculation as it was identified to significantly increase pre-camber, even at an early age. Laboratory tests were conducted to obtain compressive strength, elastic modulus, creep and shrinkage of concrete. These properties were used in the evaluation of pre-camber. The accuracy of the prediction was compared against the actual pre-camber measured on four post-tensioned ‘I’ beam with overall height of 1.98m and 36m in length for a duration of 15 days after the application of prestressing force. Based on the comparison, the improved method seems to provide better results compared to the commonly adopted simplified method. The suitability of the concrete properties, especially creep coefficient recommended by various foreign standard codes - BS 8110, EC 2, ACI and AS 3600 for application on local concrete is also examined. The method presented is readily available for local engineers to adopt